Mixed convection boundary layer flow on a vertical flat plate in Al2O3−Ag/water hybrid nanofluid with viscous dissipation effects - Elfiano, Eddy; Nik Mohd Izual, Nik Ibrahim; Muhammad Khairul Anuar, Mohamed (Semarak Ilmu Publishing, 2024)
The present research examined the mixed convection boundary layer flow and heat transfer of hybrid nanofluid on a vertical flat plate with various volume concentrations and viscous dissipation effects. The governing non-linear partial differential equations are first transformed to a system of ordinary differential equations through the use of a similarity transformation. Subsequently, these equations are solved numerically using the Runge-Kutta-Fehlberg (RKF45) method in MAPLE. The numerical solution is computed for the temperature profiles, velocity profiles, reduced Nusselt number and reduced skin friction coefficient. The characteristics of flow and heat transfer for the Eckert number, the mixed convection parameter, and the hybrid nanoparticles volume fraction are analyzed and discussed. Numerical analysis demonstrates that increases in the λ value results in a decreasing in the thickness of the thermal boundary layer, Also, variations in the Ec values have no effect on the velocity profiles. The Ag-Al2O3/ water-based hybrid nanofluid examined in this study achieves comparable results to the Ag-water-based nanofluid.